2023
DOI: 10.1111/ceo.14227
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of success for combined iStent inject trabecular bypass implantation with phacoemulsification in the subsequent eye

Abstract: Background: To investigate in combined iStent inject implantation with phacoemulsification carried out bilaterally, whether intraocular pressure (IOP)lowering effectiveness in the first eye has a predictive potential for the outcome of the second eye in primary open-angle glaucoma (POAG).Methods: This retrospective study included 72 eyes from 36 participants, who underwent trabecular bypass implantation in combination with cataract surgery at two study centres (Düsseldorf, Cologne). Surgery was classified as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In the literature, one can find a comparison of the effectiveness of the implantation of an iStent alone or with simultaneous cataract surgery. In some studies, the results suggest that reducing the IOP in patients with POAG is sufficient using iStent implantation alone (42), while other researchers have found greater benefits when the two procedures are combined (19,(43)(44)(45). When comparing cataract surgery alone with glaucoma surgery, studies have shown that the second method gives better results (35).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, one can find a comparison of the effectiveness of the implantation of an iStent alone or with simultaneous cataract surgery. In some studies, the results suggest that reducing the IOP in patients with POAG is sufficient using iStent implantation alone (42), while other researchers have found greater benefits when the two procedures are combined (19,(43)(44)(45). When comparing cataract surgery alone with glaucoma surgery, studies have shown that the second method gives better results (35).…”
Section: Discussionmentioning
confidence: 99%